2020
DOI: 10.1186/s13046-020-01773-x
|View full text |Cite
|
Sign up to set email alerts
|

Histone tail analysis reveals H3K36me2 and H4K16ac as epigenetic signatures of diffuse intrinsic pontine glioma

Abstract: Background Diffuse intrinsic pontine glioma (DIPG) is an aggressive pediatric brainstem tumor. Most DIPGs harbor a histone H3 mutation, which alters histone post-translational modification (PTM) states and transcription. Here, we employed quantitative proteomic analysis to elucidate the impact of the H3.3K27M mutation, as well as radiation and bromodomain inhibition (BRDi) with JQ1, on DIPG PTM profiles. Methods We performed targeted mass spectrome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 58 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Given their key involvement in carcinogenesis, histone PTMs are emerging as potential biomarkers in clinical diagnostics and prognostics of cancer as well as therapeutic targets 23 . While most work studying histone PTMs are carried out on tumor resection or cells lines 24 26 , we propose here a new method to identify and quantify epigenetic alterations directly from the blood of patients. Using the combination of the capture of circulating nucleosomes and the underlying analysis of histone PTMs by tandem mass spectrometry, we significantly reduced the abundance of blood proteins, allowing the characterization of histone PTMs in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Given their key involvement in carcinogenesis, histone PTMs are emerging as potential biomarkers in clinical diagnostics and prognostics of cancer as well as therapeutic targets 23 . While most work studying histone PTMs are carried out on tumor resection or cells lines 24 26 , we propose here a new method to identify and quantify epigenetic alterations directly from the blood of patients. Using the combination of the capture of circulating nucleosomes and the underlying analysis of histone PTMs by tandem mass spectrometry, we significantly reduced the abundance of blood proteins, allowing the characterization of histone PTMs in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…DIPG tumours bearing H3K27M induce a dramatic reduction in the global levels of H3K27me3 in DIPG cells [4]. Recently, other PTMs were identified, including H3K26me2 and H416ac [31]. Herein, we did not have the bioinformatics tools to determine the association between histone PTMs and H19 expression, but this would be very interesting and the objective of future studies.…”
Section: Discussionmentioning
confidence: 98%
“…These mutations are not common, but have been suggested to be associated with DIPG-H3K27M; however, their implication in DIPG progression and their link with H3K27M are poorly understood [4,21]. Other chromatin changes are controlled by dynamic post-translational modifications (PTMs) on the histone N-terminal tail, which influence the structure of chromatin and, hence, gene expression [31]. DIPG tumours bearing H3K27M induce a dramatic reduction in the global levels of H3K27me3 in DIPG cells [4].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy combined with histone methyltransferase G9a inhibitor was designed to reduce H3K9me3 levels and DSB repair. Radiotherapy can induce some histone-modified cell-specific and peptide-specific changes, which should be paid attention to when using modifiers [ 50 ]. It has been suggested that radiation kills a large number of cancer cells and induces radiation resistance and more aggressive epigenetic phenotypes.…”
Section: Epigenetics In Cancer Occurrence and Cancer Radiotherapymentioning
confidence: 99%